The Systematic Review of Diagnosis and Management of Acute Appendicitis in Adults - Averina Sutoko; Venansius Alvent; Sean Gerry Santoso (International Medical Journal Corp. Ltd, 2026)
Introduction: Acute appendicitis remains one of the most common surgical emergencies worldwide, traditionally managed by appendectomy. In recent decades, the paradigm has shifted towards exploring non-operative management with antibiotics and refining diagnostic and surgical approaches. This systematic review synthesizes contemporary evidence on the diagnosis and management of acute appendicitis in adults (Rushing et al., 2019). Methods: A systematic review was conducted by screening literature from multiple databases. Inclusion criteria encompassed studies involving adult patients (≥18 years) with suspected or confirmed acute appendicitis, evaluating diagnostic methods or management strategies, employing robust study designs (RCTs, cohort studies, systematic reviews, etc.), reporting clinically relevant outcomes, and representing unique publications. Data were extracted on study design, patient population, diagnostic and management approaches, outcomes, clinical context, and study quality from 80 included sources (Salminen et al., 2015; Coda Collaborative et al., 2020). Results: Computed Tomography (CT) is the most accurate diagnostic modality (sensitivity 92.7-97.2%, specificity 94.2-96.1%), significantly reducing negative appendectomy rates (Weston et al., 2005; van Randen et al., 2008). For uncomplicated appendicitis, antibiotic therapy is a viable but less effective alternative to surgery, with a one-year success rate of approximately 72.7% declining to 60.9% at five years (Salminen et al., 2018). The presence of an appendicolith is a critical predictor of antibiotic failure and higher complication rates (Coda Collaborative et al., 2020). Laparoscopic appendectomy is superior to open surgery, offering reduced infections and shorter hospital stays, especially in the elderly (Athanasiou et al., 2017; Southgate et al., 2012). Delayed appendectomy and outpatient management are safe and effective strategies (Patel et al., 2023; Jordi Elvira Lopez et al., 2022). Discussion: The evidence supports a tailored, patient-centered approach. Antibiotic therapy is a reasonable first-line option for uncomplicated appendicitis without an appendicolith, particularly when surgery is contraindicated or declined, offering cost savings and comparable long-term quality of life despite higher recurrence and readmission rates (Haijanen et al., 2019; Sippola et al., 2020). Appendectomy remains the definitive treatment, especially for those with an appendicolith or complicated disease. Advances in minimally invasive surgery and optimized perioperative care have improved outcomes. Conclusion: The management of acute appendicitis in adults has evolved from a purely surgical model to an individualized strategy incorporating accurate CT imaging, risk stratification (notably for appendicolith), and shared decision-making between antibiotics and surgery. Laparoscopic appendectomy is the preferred surgical approach. Future research should focus on long-term outcomes, optimization of outpatient antibiotic regimens, and protocols for low-resource settings.